2013
DOI: 10.1016/j.scitotenv.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to predicting environmental transfer of radionuclides to wildlife: A demonstration for freshwater fish and caesium

Abstract: The NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. AbstractThe application of the concentration ratio (CR) to predict radionuclide activity concentrations in wildlife from those in soil or water has become the widely accepted approach for environmental assessments. Recently both the ICRP and IAEA have produced compilations of CR values for application in environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 35 publications
(35 reference statements)
1
18
1
Order By: Relevance
“…Whilst, the CR wo-soil values for stable Cs in Table 6 are considerably lower in all cases than those reported in ICRP (2009) (Copplestone et al in-press) underlying the ICRP (2009) recommendations by Beresford et al (2013) and Wood et al (in-press) have demonstrated differences between stable and radioisotope CR wo-media values although the authors note that there may be a variety of reasons for these observations (e.g. geographical bias in the data).…”
Section: Stable Cs Compared With 137 Csmentioning
confidence: 58%
See 1 more Smart Citation
“…Whilst, the CR wo-soil values for stable Cs in Table 6 are considerably lower in all cases than those reported in ICRP (2009) (Copplestone et al in-press) underlying the ICRP (2009) recommendations by Beresford et al (2013) and Wood et al (in-press) have demonstrated differences between stable and radioisotope CR wo-media values although the authors note that there may be a variety of reasons for these observations (e.g. geographical bias in the data).…”
Section: Stable Cs Compared With 137 Csmentioning
confidence: 58%
“…How such site specific 'reference' data will be utilised within the ICRP's framework requires further elaboration and we understand that the ICRP are in the process of doing this. Beresford et al (2013) suggest an alternative approach to the CR using a residual maximum likelihood mixed model regression to derive relative values for different taxonomic groups taking into account inter-site variation. They hypothesise that the radionuclide activity concentration in a given species could be estimated from the known concentration in a different species removing the need to base predictions on media concentrations and the consequent effect of site-specific factors such as soil or water chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are alternative approaches to predict transfer to wildlife in development, such as the use of taxonomic relationships (e.g. Beresford et al, 2013Beresford et al, , 2015, most of the available tools use concentration ratios (CR wo-media ) relating the activity concentrations in plants and animals to those in the appropriate environmental media (soil, air or water) (Beresford et al, 2008a). Whilst databases of CR wo-media values for wild species have been collated (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The database provides a highly valuable resource with which to explore trends in datasets providing the basis for statistical analyses (e.g. Beresford et al, 2013;Wood et al, 2013). The WTD and the IAEA and ICRP compilations summarise data across all isotopes for a given element (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A more analytical means of exploring the validity of this approach by looking at relationships between CRs for various taxa would clearly be advantageous. One potentially useful approach is based upon the hypothesis that some form of underlying taxonomic and/or phylogentic relationship exists in relation to ecological transfer of radionuclides (Beresford et al, 2013).…”
Section: Introductionmentioning
confidence: 99%